How does leader-member exchange differentiation affect the creativity of nursing teams in the medical tourism industry: the roles of status conflict, knowledge sharing, and justice climate - Hua Yang; Rujie Chen; Yiyun Ying (Leadership & Organization Development Journal, 2026)
Purpose Medical tourism poses numerous challenges to healthcare teams worldwide. Under the dual pressures of advancing medical technology and surging demand for high-quality services, enhancing nursing team creativity has become key to meeting these challenges. Throughout this process, leader-member exchange (LMX) permeates every aspect of nursing teams' innovation activities. However, due to leaders' limited resources and strategic considerations, leader-member exchange differentiation (LMXD) has become a common phenomenon that team members must navigate, which, in turn, exerts complex effects on nursing team creativity. Design/methodology/approach Based on 407 valid questionnaires, this study employs Mplus 8.0 to explore the internal mechanism underlying the relationship between LMXD and nursing team creativity. Findings The research findings are as follows: (1) There exists a negative correlation between LMXD and nursing team creativity; (2) Status conflict serves as a mediating factor between LMXD and nursing team creativity; (3) Knowledge sharing acts as a mediating variable between LMXD and nursing team creativity; (4) Status conflict and knowledge sharing play a chained-mediating role between LMXD and nursing team creativity; (5) Justice climate has a moderating effect on the relationship between LMXD and nursing team creativity. Originality/value The relevant conclusions can enrich human-resource management theories and provide valuable guidance for hospitals and nursing services in medical tourism to boost HR efficiency and nursing team creativity.